Primary production and plankton assemblages in the fisheries ground around San Jorge Gulf (Patagonia) during spring and summer - Segura, Valeria (2021)
The San Jorge Gulf, and the littoral to its north, is one of the most important fishing grounds for Argentina. Nevertheless, phytoplankton production has been scarcely studied. Here we analyzed during spring (2008) and summer (2009) the phytoplankton biomass, production, and the composition of phytoplankton and protozooplankton; their possible trophic relationships, and physical conditioners. At the south coast of the gulf during spring micro-nano-plankton (diatoms and dinoflagellates) were predominant and responsible for the maximum integrated production, comparable to that reported for the rich Argentinian shelf-break. Part of the organic carbon produced there was consumed by heterotrophic dinoflagellates, adding a trophic level to the food web. While at the center of the gulf, a conspicuous deep chlorophyll maximum would probably add organic matter to the bottom. During the following summer (2009), the ultrafraction represented the largest contribution to total phytoplankton biomass, and was dominated by Synechococcus sp. This, plus the abundance of ciliates, indicate the prevalence of a microbial food web during summer. It has been found that the frontal zones in the north and south of the gulf, favoring high phytoplankton biomass and its maintenance due to high primary production, provide a favorable food environment for impregnated female shrimp in spring, and for larvae during summer.